An evaluation of good governance in US Olympic sport National Governing Bodies. Issue 4 (7th August 2020) - Pielke, Roger; Harris, Spencer; Adler, Jared; Sutherland, Sara; Houser, Richard; McCabe, Jackson
ABSTRACT: Research question This paper applies the Sports Governance Observer (SGO) methodology to 47 US Olympic NGBs (National Governing Bodies) of sport and discusses the utility of such constructs. Research methods The SGO methodology was applied to the 47 US Olympic NGBs of sport. This methodology focuses on publicly available information and scores NGB performance in line with standardised criteria. An overview of NGB responses is presented based on the researchers' experiences working with NGB representatives after presenting the preliminary findings of the SGO. An assessment of the utility of the SGO construct was developed based on the experience of applying the SGO standardised methodology. Results and findings We found a wide range of scores across the NGBs with a high score of 81 (out of 100) and a low of 41, with an average of 58 and a median score of 59. We critique the limitations and value of such indicators and constructs in the context of good governance and discuss the implications for Olympic sport governance. Implications Whilst the SGO has value it is also accompanied by some significant limitations. It is important for researchers, practitioners and policy-makers to work collectively to ensure that measures of good governance extend beyond what an organisation might choose to present to the public and to examine the cultures, leadership and behaviours that underpin such issues.